Conjugated Polyelectrolytes: Underexplored Materials for Pseudocapacitive Energy Storage. Issue 22 (8th October 2021) - Quek, Glenn; Roehrich, Brian; Su, Yude; Sepunaru, Lior; Bazan, Guillermo C.
Abstract: Conjugated polyelectrolytes (CPEs) are characterized by an electronically delocalized backbone bearing ionic functionalities. These features lead to properties relevant for use in energy‐storing pseudocapacitor devices, including ionic conductivity, water processability, gel‐formation, and formation of polaronic species stabilized by electrostatic interactions. In this Perspective, the basis for evaluating the figures of merit for pseudocapacitors is provided, together with the techniques used for their evaluation. The general utility and challenges encountered with neutral conjugated polymers are then discussed. Finally, recent advances on the use of CPEs in pseudocapacitor devices are reviewed. The article is concluded by discussing how their miscibility in aqueous media permits the incorporation of CPEs in living materials that are capable of switching function from extraction of energy from bacterial metabolic pathways to pseudocapacitor energy storage. Abstract : Conjugated polyelectrolytes are characterized by an electronically delocalized backbone bearing ionic functionalities. These features lead to properties relevant for use in energy‐storing pseudocapacitor devices, including ionic conductivity, water processability, gel formation, and formation of polaronic species stabilized by electrostatic interactions. Moreover, that conjugated polyelectrolytes are miscible in aqueous media enables living materials that can switch from energy production to energy storage.